Development of E-LKM Inquiry Learning oriented STEM Respiration and Photosynthesis Materials to Improve Science Literacy and Student Investigation Ability - Intan Elvianti Agustina; Suyitno Aloysius (Journal of Science Education Research, 2026)
This study aims to produce E-LKM Inquiry learning media oriented STEM towards respiration and photosynthesis materials that are appropriate, practical, and effective in increasing science literacy and student investigation capabilities. This research is a study and development (R&D) with the Addie model. In this study, it was not only a trial in a small scale, but also a large scale test was conducted using the Non-Equivalent Control Group quasi-experimental design in 62 students divided into experimental and control groups. The instrument used was in the form of a scientific literacy test and a student investigation capability questionnaire. Data analysis was carried out using the Manova test. The results showed that the E-LKM Inquiry Learning is STEM-oriented and practical to support the learning process with a very good category, based on validation by media experts and materials and based on the assessment of educators and students. In addition, E-LKM Inquiry Learning oriented STEM also affects in increasing science literacy and students' investigation abilities simultaneously from GIS grades. Manova test of 0,000 (<0.05). In conclusion, the E-LKM Inquiry Learning oriented STEM is declared feasible, practical, and effectively used in learning, especially in respiration and photosynthesis material. This media is proven to be able to increase science literacy and students' investigation abilities simultaneously.